Modelling Tundra Ponds as Initiators of Peat Plateau Thaw, Northern Hudson Bay Lowland, Manitoba - Dyke, Larry D.; Sladen, Wendy E. (The Arctic Institute of North America, 2022)
Frozen peat in permafrost regions poses a potential source of increased greenhouse gas production should these deposits thaw. Ponds on frozen peat plateaus in northern Manitoba are numerically modelled as heat sources to determine their potential to promote thaw. Modelling indicates that anticipated climate warming of approximately 2˚C between 2020 and 2050 will produce taliks up to a few metres thick beneath ponds a few tens of metres across. However, active-layer thickness in the subaerial parts of peat plateaus will not increase beyond the peat thickness. These findings assume 1) a climate warming rate under a moderately effective intervention in greenhouse gas production, 2) pond freezing regimes that represent both rapid ice formation and ice formation delayed by rapid snow accumulation, and 3) snow thermal conductivities that anticipate snow conductivity increase during the freeze interval. These conditions and properties may turn out to be less conducive to talik expansion than the values that will actually occur. Despite these uncertainties, peat plateau pond sizes and plateau margin positions can be monitored to ascertain the onset of accelerated thawing. La tourbe gelée des régions de pergélisol pourrait constituer une source de production accrue de gaz à effet de serre si ces dépôts dégelaient. Les étangs des plateaux tourbeux gelés du nord du Manitoba font l’objet d’une modélisation numérique en tant que sources de chaleur afin de déterminer la possibilité qu’ils déclenchent un dégel. Selon la modélisation, le réchauffement climatique d’environ 2 ˚C prévu de 2020 à 2050 aura pour effet de produire des taliks de quelques mètres d’épaisseur sous les étangs, sur quelques dizaines de mètres de largeur. Cependant, l’épaisseur de la couche active des parties subaériennes des plateaux tourbeux n’augmentera pas au point de dépasser l’épaisseur de la tourbe. Ces constatations présument : 1) un taux de réchauffement climatique correspondant à une intervention modérément efficace en matière de production de ...